PEMANFAATAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS CANVA DENGAN MENGGUNAKAN SMARTBOARD UNTUK MENINGKATKAN LITERASI SASTRA ANAK DI SEKOLAH DASAR - Harsy, Emirah Afifah; Habli, Fadhilah; Adrias, Adrias; Chandra, Chandra (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The use of digital technology in learning in elementary schools is now an urgent need to answer literacy challenges, especially in the field of literature. This study aims to examine the potential and effectiveness of the use of Canva-based interactive learning media in improving the literary literacy of elementary school students. The research method used is literature review. Data was collected through a search of scientific articles, books, and related documents from digital databases such as Google Scholar and Mendeley with a publication time span of 2021-2026. The data analysis method is carried out through literature review through the stages of data collection, data presentation, and conclusion drawn. The results of the literature review show that Canva has an inclusive design feature that is able to turn abstract literary material into concrete visualizations to be presented via a smartboard. A synthesis of various studies shows that Canva's integrated integration with touch features on smartboards in literary learning can significantly improve students' reading comprehension, narrative comprehension, and creativity. The conclusion of this study confirms that the use of Canva-based interactive media displayed on a smartboard is an innovative solution that is relevant to strengthen the foundation of literary literacy at the elementary school level through direct interaction between students and technology in the digital age.